CONSEQUENCES OF IMPROPER INFANT FEEDING - I.N. Zakharova; E.V. Lykina ("Paediatrician" Publishers LLC, 2007)
The article deals with the concept of food programming according to which the type of nourishment of an infant programs peculiarities of his metabolism all along his entire future life, and as a consequence, predisposition to certain diseases and characteristics of their run. The work gives an estimate of the hazards and consequences of improper infant feeding and explains the advantages of the breast feeding. The authors present modern information on preparation of baby milk formulas. Key words: infants, health, feeding, adapted milk formulas, nucleotides, long chain polyunsaturated fatty acids, oligosaccharides.